Systems, Smart Technologies, and Innovation for Society: Proceedings of CITIS 2024 (Lecture Notes in Networks and Systems, 2025)
This open access book compiles the proceedings of the tenth edition of the International Congress on Science, Technology and Innovation for Society, a key event that addresses in a practical and multidisciplinary way smart technologies and their impact on crucial sectors such as sustainability, environment, information and telecommunications, industry and mobility. Through studies with diverse methodologies, basically applied research, it explores how emerging technologies such as artificial intelligence, machine learning, the Internet of Things and big data are transforming these fields, solving global problems and improving the quality of life. It should be noted that the novelty of the book lies in presenting research that integrates the perspectives of experts from different sectors, combining the technical vision with the analysis of the social, economic and environmental impacts of technological innovation. In this sense, it has a broad scope, as it is aimed at professionals, researchers and students of technology, engineering, data science, sustainability, etc., as well as entrepreneurs and public policy makers. It is also a valuable resource for those interested in understanding how emerging technologies can transform key sectors and contribute to a more sustainable future, from informed decision making in the fields of scientific research, technological innovation; as well as being a source of inspiration for entrepreneurs and project leaders seeking cutting-edge technological solutions. In short, a key work for those who wish to explore the future of smart technologies and their impact on society.